2012
DOI: 10.1111/j.1365-2427.2012.02788.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat persistence for sedentary organisms in managed rivers: the case for the federally endangered dwarf wedgemussel (Alasmidonta heterodon) in the Delaware River

Abstract: Summary 1. To manage the environmental flow requirements of sedentary taxa, such as mussels and aquatic insects with fixed retreats, we need a measure of habitat availability over a variety of flows (i.e. a measure of persistent habitat). Habitat suitability measures in current environmental flow assessments are measured on a ‘flow by flow’ basis and thus are not appropriate for these taxa. Here, we present a novel measure of persistent habitat suitability for the dwarf wedgemussel (Alasmidonta heterodon), lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…River slope and water depths were not measured at site 1. Maloney et al (2012) indicated that water depth, current velocity, and shear stress at site 1 are similar to site 2 during river discharge (less than about 100 m 3 s −1 ). Cole et al (2008) also indicated similar water depths between sites 1 and 2 in portions of the riverbed where DWM are known to be present.…”
Section: Geomorphic Parametersmentioning
confidence: 90%
See 2 more Smart Citations
“…River slope and water depths were not measured at site 1. Maloney et al (2012) indicated that water depth, current velocity, and shear stress at site 1 are similar to site 2 during river discharge (less than about 100 m 3 s −1 ). Cole et al (2008) also indicated similar water depths between sites 1 and 2 in portions of the riverbed where DWM are known to be present.…”
Section: Geomorphic Parametersmentioning
confidence: 90%
“…Each site encompassed areas where DWM were found as well as similar adjacent or nearby areas where DWM had never been found. Previous studies at these same three sites investigated minimum flows and temperature stability (Cole et al, 2008) and modeled shear stress related to occurrence of DWM (Maloney et al, 2012). Site 1 extends along the right (descending) side of a mid-channel island (Fig.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…A higher number of mollusc species was recorded in the Wkra River, the width of which ranges from 0.5 to 60.0 m, than in its tributaries (width 0.8-15.0 m). According to Pérez-Quintero (2007) and MaLoney et al (2012, mussels, especially Unionidae, are sensitive to variation in hydrological conditions (lower-higher flows, velocity, river depth, bed stability) and prefer the permanent lowland watercourses of rivers. Thus, the higher number of unionid mussel species in the Wkra River may be explained by its less variable conditions compared to its tributaries.…”
Section: Mollusc Communities In Relation Tomentioning
confidence: 99%
“…In rivers, it may be the result of the interaction between alkalinity and the stream drainage area (DILLon & benfIeLd 1982), algal biomass, flow rate, substrate particle sizes, depth (crowL & schneLL 1990), hydrological conditions, or bed stability (MaLoney et al 2012). Distribution may also be a function of food supply (dILLon & benfIeLd 1982), conductivity, permanence, river width, turbidity (Pérez-Quintero 2011), environmental calcium concentration (BrIers 2003) or nutrient enrichment and periphyton abundance (HardIng et al 1999).…”
Section: Mollusc Communities In Relation Tomentioning
confidence: 99%